Alterações causadas pelo fogo na vegetação e seus efeitos sobre os padrões de forrageio das formigas-cortadeiras-de-folhas no Cerrado - Silva, Jaqueline Vaz da (2021)
Environmental disturbances disturb the structure and composition of communities, affecting the availability of resources and the animals' diet. These disturbances can favor certain species of animals. Leaf-cutter ants or saúvas are generalist herbivores, with the ability to use different plant resources as a fungal substrate. These ants adjust their foraging according to the environmental conditions where they live. In disturbed environments, such as regenerating forests or forests with an edge effect, saúvas are generally favored and there are reports of an increase in the number of colonies. In these environments, this is due to the greater abundance of pioneer species, plants that are more palatable and preferred by these ants. Thus, ants tend to collect more plant material, mainly exploiting pioneer species. In the savanna environment of the Cerrado biome, fire is a natural disturbance that can impact available plant resources and cause variations in microclimatic conditions. In this sense, I investigated how fire disturbance affects the foraging activity of the Atta laevigata species in the Cerrado, even after two years of the vegetation burning event. Among the results found: fire did not affect the richness or abundance of plants, but caused a significant change in the floristic composition. Apparently, this change in the foraging area of the colonies was characterized by a reduction in the general quality of vegetation for the saúvas. In addition, the same pattern was recorded in the trail system for both areas (burned and unburned) and foraging activity occurred under the same variations in temperature and relative humidity. However, the colonies in the burned area showed a greater asynchrony in their activity, with a smaller flow of ants being recorded on the trails, culminating in a smaller amount of collected plant fragments. In this context, the changes caused by fire disturbance in the Cerrado seem not to be favorable to saúvas, in line with what has been reported in disturbed forest environments.